Avaliação da expressão transiente do gene da glicoproteína do vírus da raiva (RVGP) em células de inseto da linhagem Drosophila melanogaster S2 - Patiño, Sandra Fernanda Suárez (Universidade Federal de São Carlos, 2011)
Rabies is a zoonotic viral disease caused by a virus of the genus Lyssavirus that affects several species of mammals. Rabies remains a global public health threat that kills more than 55,000 people per year mainly in developing countries, this disease once established do not have a specific treatment. The RV envelope is composed of a glycoprotein, known as a unique antigen capable of conferring immune response against the rabies, and therefore, is the focus of research for development an efficient and safe recombinant vaccine based on this viral antigen. Cell line stably transfected S2 Drosophila melanogaster have been used in the production of many heterologous proteins and has been studied for the production of the rabies virus glycoprotein (RVGP) in our laboratory. This approach involves the selection of high producing cell populations; procedure that requires considerable periods of time (months), increasing management and costs of production. In this sense, in recent decades, many systems focused on the expression of heterologous proteins by transient expression of genes, were analyzed because they allow obtaining significant quantities of recombinant protein in a short period of time (weeks). For the use of transient transfection technology can be found a variety of methods and available agents, such as electroporation, cationic lipids, cationic polymers and calcium phosphate precipitated. The choice and optimization of each of them depends mainly on the cell type and protein being expressed. Thus, the objective of this study was to evaluate the transient expression of the glycoprotein gene of rabies virus (RVGP) in insect cells of Drosophila melanogaster S2 lineage, evaluating the vehicles transfection: calcium phosphate, cationic lipid (Cellfectin) and cationic polymer (ExGen500 and JetPEI). In order to determine the most efficient transfection agent, experiments were performed in 6 well plate and bottle of 100 mL of culture, which analyzed the influence of cell density, the concentration of DNA and transfection reagent volume on the expression of RVGP assessed by ELISA and fluorescence microscopy. Yields ranging from 50-90 ng/107cel were obtained in different experiments on multiwell plate, suggesting strong effect of ratio DNA: transfection agent used. Comparison of transfection agents showed no significant differences. In transfections made in suspension culture was analyzed the effect of the plasmid (whether or not the signal of BiP cell secretion) on the expression RVGP. When we used the plasmid containing the signal BiP (pMTiRVGP) were obtained 160 ng/107cel of RVGP production, and 200 ng/mL of volumetric production without significant differences between the different transfection agents. However, significant differences were found when we used the plasmid not containing the signal BiP (pMTRVGP), with the RVGP production was 60 ng/107cells in cells transfected with Cellfectin, ExGen500 and calcium phosphate, except in cells transfected with JetPEI was reached a production of 120 ng/107cells. In preliminary experiment bottle type "spinner" with a working volume of 60 mL were achieved expressions of 140 ng/107cel of RVGP in cells transfected with JetPEI and calcium phosphate. This suggests that optimization of culture conditions and transfection are possible to increase recombinant protein expression in cultured on a large scale.
Keywords: Biotecnologia; Drosofila melanogaster; Expressão transiente; Glicoproteína da raiva; Fosfato de cálcio; Transfecção; PEI; Drosophila melanogaster S2 cells; Rabies virus glycoprotein RVGP; Calcium phosphate; PEI; Transfection; CIENCIAS BIOLOGICAS::BIOQUIMICA